Іт and virtual warfares: effects of gaming technologies - Berezhna, O. B. (ТОВ «Друкарня Мадрид», 2024)
Computer games are an extremely popular form of entertainment, attracting millions of players with their dynamic gameplay and the ability to interact with the virtual world.
Keywords: virtual world; virtual warfares